Effect of Deep Learning Approach With GeoGebra-Based Interactive PowerPoint and Animated Videos on Concept Understanding - Silvina, Nur; Tumanggor, Abednego Pradja; Tarigan, Adelia Br; Lubis, Dara Muna; Sibarani, Mikhael Agus Tua; Siregar, Budi Halomoan (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This study focused on identifying the magnitude of the impact of a deep learning approach assisted by GeoGebra-based interactive PowerPoint media and animated videos on junior high school students’ conceptual understanding, particularly on the topic of straight-line equations. The research employed a quasi-experimental methodology with a pretest–posttest design involving two groups: the experimental group and the comparison group. The measurement instruments consisted of essay questions, and the data were analyzed using normality testing, homogeneity testing, and an independent t-test. The findings revealed a significant improvement in the experimental group’s conceptual understanding. The higher average posttest score compared to the control group confirmed that the use of interactive media enhanced students’ understanding of the material in a more visual and engaging way. Furthermore, the deep learning strategy optimized students’ active involvement in understanding and connecting relevant material to real-life situations. Thus, the synergy between digital media and this learning strategy was proven to effectively enhance conceptual understanding.